Characterisation and expression analysis of two terminal complement components: C7 and C9 from large yellow croaker, Larimichthys crocea. (April 2016) - Guo, Baoying; Wu, Changwen; Lv, Zhenming; Liu, Changlin
Abstract: The large yellow croaker Larimichthys crocea, as one of the most economically important marine fish in China and East Asian countries, are facing the fatal attraction of various pathogens in recent years. Elucidation of the organism immunomodulatory mechanism of croaker response to pathogen infection is essential for the disease control. In present study, we reported for the first time the molecular characterization and expression analysis of two terminal complement components (TCCs) of croaker, Lc-C7 and Lc-C9 . These two structural conserved TCCs were detected in many tissues in adult healthy fish, with highest levels detected in liver. The transcriptional expression analysis of Lc-C7 and Lc-C9 at different developmental stages showed a continuous increase towards hatch, however the two TCCs mRNA were not detected at the unfertilized stage, hinting the origination of these two TCCs after fertilization. Rapid and drastic responses to Vibrio alginolyticus challenge were observed for Lc-C7 and Lc-C9, suggesting the involvement of component C7 and C9 in innate immune responses to pathogenic invasion in teleost fish. These findings could deepen our understanding about immunomodulatory mechanisms of croaker and shed a new light to the role of component system in teleostean immunomodulation. Highlights: The seventh and ninth complements were first cloned and characterized in croaker. Distribution, ontogeny and reaction to challenge of two TCCs were analyzed. Phylogenetic relationships of two TCCs were analyzed.